Pengaruh Model Pembelajaran Problem Solving Laboratory Terhadap Hasil Belajar Fisika SMA Pada Materi Penerapan Persamaan Gerak Harmonis Sederhana - Chairatul Umamah; Maisyatul Azkiyah; Herman Jufri Andi; Suprianto Suprianto (Department of Physics Education, Universitas Mataram, 2021)
The purpose of this study are to determine whether there was a significant effect of the application of the Problem Solving Laboratory learning model on high school physics learning achievement and to identify improvements in high school physics learning achievement by using the Problem Solving Laboratory learning model. This research is a quasi-experimental research with non-equivalent control group design. The population of this study is the entire class X even semester of MA Al-Islamiyah 1 Sumber Batu Blumbungan Larangan Pamekasan, while the samples are 2 classes X IPA consist of 22 students each selected using purposive sampling technique. Based on the results of hypothesis testing using the Independent Sample T-test test in the SPSS V. 25 program, obtained a value ofÃÂ ÃÂ > ÃÂ (4.334 > 2.018) and a sig value (2-tailed) = 0.000 or < 0.05 so it can be concluded that there is a significant effect of application of the Problem Solving Laboratory learning model to high school physics learning achievements. The results of data analysis using the N-Gain test showed the N-gain value in the experimental class was 0.7823 or G > 0.7. Thus, it is concluded that the improvement of high school physics learning achievements using the Problem Solving Laboratory learning model is in the high category.